2015
DOI: 10.1186/s12864-015-2133-9
|View full text |Cite
|
Sign up to set email alerts
|

Root iTRAQ protein profile analysis of two Citrus species differing in aluminum-tolerance in response to long-term aluminum-toxicity

Abstract: BackgroundLimited information is available on aluminum (Al)-toxicity-responsive proteins in woody plant roots. Seedlings of ‘Xuegan’ (Citrus sinensis) and ‘Sour pummelo’ (Citrus grandis) were treated for 18 weeks with nutrient solution containing 0 (control) or 1.2 mM AlCl3 · 6H2O (+Al). Thereafter, we investigated Citrus root protein profiles using isobaric tags for relative and absolute quantification (iTRAQ). The aims of this work were to determine the molecular mechanisms of plants to deal with Al-toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
47
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 74 publications
13
47
2
2
Order By: Relevance
“…This disagrees with our reports that more Al-responsive proteins related to protein metabolism were identified in C. sineneis than in C. grandis roots (Jiang et al, 2015). Most of these genes were involved in protein degradation, followed by protein ubiquitination-related genes, heat shock protein (HSP)/chaperone genes and protein biosynthesis-related genes.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This disagrees with our reports that more Al-responsive proteins related to protein metabolism were identified in C. sineneis than in C. grandis roots (Jiang et al, 2015). Most of these genes were involved in protein degradation, followed by protein ubiquitination-related genes, heat shock protein (HSP)/chaperone genes and protein biosynthesis-related genes.…”
Section: Discussioncontrasting
confidence: 99%
“…This agrees with the report that both JA biosynthesis and level might be elevated in +Al C. sinensis roots (Jiang et al, 2015). Peixoto et al (2001) reported that both LOX activity and Al-induced increase in LOX activity were greater in Al-tolerant than in Al-sensitive sorghum cultivar.…”
Section: Discussionsupporting
confidence: 93%
“…However, Se is known to have a beneficial effect when present in low concentrations (Pilon-Smith et al 2009). Several studies have demonstrated multiple impacts of Se on plant physiology, such as increased biomass production (Chen et al 2014, Jiang et al 2015, Feng et al 2016, delayed senescence (Xue et al 2001), increased tolerance to oxidative damage (Feng et al 2013, Diao et al 2014, Qing et al 2015, Tang et al 2015, increased production of carotenoid pigments (Ning et al 2016), higher tolerance to photooxidative stresses (Seppänen et al 2003), greater carbohydrate accumulation (Turakainen et al 2006, Owusu-Sekyere et al 2013, and alleviation of the effects of biotic and abiotic stresses (Hanson et al 2003, Yao et al 2010, Hasanuzzaman and Fujita 2011, Han et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of Se can damage the photosynthetic apparatus, inhibit photosynthesis, and reduce starch production (Vítová et al 2011, Łabanowska et al 2012, Wang et al 2012. However, in adequate concentrations, Se can enhance photosynthesis and protect the PSII (Feng et al 2015, Jiang et al 2015. Previous studies have shown that chlorophyll (Chl) a fluorescence analysis is an efficient nondestructive technique to evaluate modulations in the photosynthetic apparatus under different environmental conditions (Zushi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…To explore some of the mechanisms underlying the generation of heterosis at the protein level, proteomic molecular analysis has been introduced over many years [17][18][19]. The abundance of a protein is not only regulated at a transcriptional level, but also at translational and post-translational levels [20], so proteomics is a very powerful tool to analyze the functions of plant proteins [21][22][23]. To identify a larger number of proteins and provide more reliable quantitative information, the iTRAQ (isobaric tags for relative and absolute quantitation) method has been introduced to execute quantitative comparison and analysis of protein expression profiles of multiple samples simultaneously [24][25][26].…”
Section: Introductionmentioning
confidence: 99%